Liquid-liquid phase separation as a major mechanism of plant abiotic stress sensing and responses - Xin Liu; Jian-Kang Zhu; Chunzhao Zhao (Stress Biology, 2023)
Abstract Identification of environmental stress sensors is one of the most important research topics in plant abiotic stress research. Traditional strategies to identify stress sensors or early signaling components based on the cell membrane as a primary site of sensing and calcium signal as a second messenger have had only limited successes. Therefore, the current theoretical framework underlying stress sensing in plants should be reconsidered and additional mechanisms need to be introduced. Recently, accumulating evidence has emerged to suggest that liquid-liquid phase separation (LLPS) is a major mechanism for environmental stress sensing and response in plants. In this review, we briefly introduce LLPS regarding its concept, compositions, and dynamics, and then summarize recent progress of LLPS research in plants, emphasizing the contribution of LLPS to the sensing of various environmental stresses, such as dehydration, osmotic stress, and low and high temperatures. Finally, we propose strategies to identify key proteins that sense and respond to environmental stimuli on the basis of LLPS, and discuss the research directions of LLPS in plant abiotic stress responses and its potential application in enhancing stress tolerance in crops.